The general law on persons with disabilities and the right to self-determination of people with mental disabilities. - Espinoza Espinoza, Juan (2015)
This law is extremely important, since repealed and modified quite a few articles of the Civil Code related to exercise capacity. Indeed, aims to establish the legal framework for the promotion, protection and realization, equal, rights of persons with disabilities, promoting their development and full and effective inclusion in the political, economic, social, cultural and technological (art. 1.°), the defines a disabled person.